Relationships Between Age, Soluble Triggering Receptor Expressed on Myeloid Cells-1 (sTREM-1), and Mortality Among Critically Ill Adults: A Cohort Study. Issue 2 (22nd February 2022) - Sathe, Neha A.; Bhatraju, Pavan K.; Mikacenic, Carmen; Morrell, Eric D.; Mabrey, F. Linzee; Liles, W. Conrad; Wurfel, Mark M.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Innate immune dysregulation may contribute to age-related differences in outcomes among critically ill adults. Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) is an important innate immune marker with prognostic value in sepsis, but age-related differences have not been studied. Methods: This was a prospective cohort from a large tertiary care hospital enrolling adults from both medical and trauma-surgical intensive care units (ICUs). Plasma sTREM-1 was measured in participants within 24 h of ICU admission. We analyzed associations between age (≤50 and >50 years) and sTREM-1 using linear regression. We then examined associations between sTREM-1 and both 28-day mortality and persistent organ dysfunction (defined as need for dialysis, vasopressors, or invasive mechanical ventilation) 7 days following admission using relative risk regression. Results: Of 231 critically ill adults, older patients (n = 122) had higher prevalence of chronic disease and sepsis on enrollment than younger patients, but acute illness severity was similar. Age over 50 was associated with 27% higher sTREM-1 concentrations (95% CI 6%–53%), adjusted for sex and Charlson comorbidity index (CCI). Two-fold higher sTREM-1 was associated with 2.42-fold higher risk for mortality (95% CI 1.57, 3.73) and 1.86-fold higher risk for persistent organ dysfunction (95% CI 1.45, 2.39), adjusted for sex, CCI, and age. Conclusions: sTREM-1 was elevated among critically ill older adults, and strongly associated with both death and persistent organ dysfunction. Immune responses associated with sTREM-1 may contribute to age-related differences in ICU outcomes, warranting further study as a potential therapeutic target in older adults.